PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP PEMAHAMAN BELAJAR PENDIDIKAN AGAMA ISLAM DI SD MUHAMMADIYAH 6 PEKANBARU - Afini Nurul Hidayat; Risnawati; M. Fikri Hamdani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore the impact of using TikTok social media on the understanding of Islamic Education (PAI) among sixth-grade students at Muhammadiyah 6 Elementary School in Pekanbaru, as well as to assess the quality of student learning after utilizing this social media platform. The methodology employed in this study is a quantitative approach, applying simple linear regression formulas. Data was collected through several techniques, including observation, questionnaires, and documentation. The sample consisted of 53 students. Data analysis was performed using simple regression formulas, while validity testing was conducted using the product moment method and reliability testing employed Cronbach's alpha.The findings indicate that the use of TikTok social media has an influence on students' understanding of PAI, evidenced by a linear regression result of 0.451. This suggests a significant impact of social media usage on the understanding of PAI among students at Muhammadiyah 6 Elementary School in Pekanbaru. Furthermore, the contribution of social media usage to understanding learning is 20.3%, with the remaining 79.7% indicating that other factors also play a role in influencing students' understanding.